Pengaruh Macam Pupuk Organik Cair (POC) dan Interval Pemberian terhadap Hasil Tanaman Mentimun (cucumis Sativus L.) var. Harmony - Historiawati (Indoensia), Hitoriawati; nur jannah (Indoensia), eka; Prasetyo (Indoensia), Fajar Aji (Universitas Tidar, 2024)
Research on the Effect of Types of Liquid Organic Fertilizer (POC) and Application Intervals on the Yield of Cucumber Plants (Cucumis sativus L.) Harmony Variety began in April 2022 – June 2022 in Gunung Bakal Hamlet, Sumberan Village, Tempuran District, Magelang Regency, Central Java. The experiment used a Randomized Complete Block Design (RAKL) with two treatment factors and three replications as blocks. The first treatment factor is the type of POC consisting of well water (P0), Jimy Ghost POC (P1), Nasa POC (P2), and Cow Rumen POC. The second treatment is the POC administration interval, 4, 7, and every 10 days. The POC-type treatment provided optimal results in fruit diameter parameters and wet stover weight parameters compared to the treatment without POC. For the parameters of fruit length, weight per fruit, fruit weight per plant, and dry weight of stover, P3 and P2 treatments gave optimal results. The POC administration interval treatment shows that the results of the data analysis only influence the photosynthesis rate test parameters by providing optimal results at a once every 4 day administration interval and do not optimally influence the results of other observation parameters. There was no interaction between the type of POC treatment and the frequency of POCKeywords : POC granting interval, result, types of POC